A rapid method for estimating the angle of repose and volume of grain piles using terrestrial laser scanning. Issue 7 (2nd July 2020) - Liu, Meijuan; Dong, Pinliang; Zhong, Ruofei
ABSTRACT: The angle of repose and volume of granular piles are important measures in many fields. This letter presents a new method for rapid estimation of the angle of repose and volume of grain piles using terrestrial laser scanning data acquired from a single site. Compared with some existing methods that require point cloud registration and surface reconstruction, the proposed method is simple and easy to use. Results from 12 buckwheat and corn grain piles suggest that the method is efficient and effective, especially when the point spacing is 3.1 mm. A relative error of less than 5% can be achieved for volume estimation of buckwheat and corn piles. The method can be applied to the estimation of the angle of repose and volume of other cone-shaped granular piles, under different environmental conditions.